1992-planning for the information technology industries (IBI international business intelligence., 1989)
1992-Planning for the Information Technology Industries provides a summary of the relevant legislation, research programs, and proposals for the establishment of a single European market for information technology (IT). The development of the European Community's (EC) policy and the implications of its implementation for the EC and third country markets are examined. The views from a number of major organizations that operate in the telecommunications, broadcasting, and information services markets are considered to provide an insight into some of the factors influencing planning for 1992. Thi.